CD5-negative mantle cell lymphoma: clinicopathologic features of an indolent variant that confers a survival advantage. Issue 4 (21st March 2022) - Soleimani, Arshia; Navarro, Alba; Liu, Delong; Herman, Sarah E. M.; Chuang, Shih-Sung; Slavutsky, Irma; Narbaitz, Marina; Safah, Hana; Schmieg, John; Lefante, John; Roschewski, Mark; Wilson, Wyndham H.; et al.
Abstract: Conventionally, mantle cell lymphoma (MCL) is an aggressive CD5-positive B-cell malignancy with poor prognosis and limited survival. However, a small subset of patients presents with indolent disease and can be managed on a 'watch and wait' approach. CD5-negative MCL has recently been recognized as a more favorable variant of MCL, but its clinical and biological implications remain ill-defined. We performed the most extensive review to-date of all reported cases of CD5-negative MCL and included unpublished cases diagnosed at our institutions to further characterize this disease subset. Based on our analysis of 356 cases of CD5-negative MCL, we conclude that median overall survival exceeds 14 years and is independent of favorable prognostic markers such as leukemic non-nodal disease, absence of SOX11, and low Ki-67.